2019
DOI: 10.1093/nar/gkz189
|View full text |Cite
|
Sign up to set email alerts
|

A 5′-to-3′ strand exchange polarity is intrinsic to RecA nucleoprotein filaments in the absence of ATP hydrolysis

Abstract: RecA is essential to recombinational DNA repair in which RecA filaments mediate the homologous DNA pairing and strand exchange. Both RecA filament assembly and the subsequent DNA strand exchange are directional. Here, we demonstrate that the polarity of DNA strand exchange is embedded within RecA filaments even in the absence of ATP hydrolysis, at least over short DNA segments. Using single-molecule tethered particle motion, we show that successful strand exchange in the presence of ATP proceeds with a 5′-to-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 99 publications
(131 reference statements)
1
8
0
Order By: Relevance
“…In previous studies, the synapse lifetime depended on the buffer (pH, ionic strength, ion species, etc.) and the length and sequence of the DNA (59,60). A synapse lifetime with a range of seconds to approximately a hundred seconds was reported, similar to our experimental results here.…”
Section: (E)supporting
confidence: 90%
See 1 more Smart Citation
“…In previous studies, the synapse lifetime depended on the buffer (pH, ionic strength, ion species, etc.) and the length and sequence of the DNA (59,60). A synapse lifetime with a range of seconds to approximately a hundred seconds was reported, similar to our experimental results here.…”
Section: (E)supporting
confidence: 90%
“…The C-terminus of RecA affects the stability of synaptic complexes in the homologous sequence searching process Our previous single-molecule analysis showed that >80% of E. coli RecA nucleoprotein filaments participate in futile interactions with dsDNA, and only <20% of collisions lead to successful DNA strand exchange reactions (35,59). For those molecules that failed to proceed into DNA strand exchange, tethers appeared only for seconds and then disappeared (Fig.…”
Section: (E)mentioning
confidence: 99%
“…The nucleoprotein filament assembles, disassembles, and promotes strand exchange with a predominant 5 0 -to-3 0 polarity. The observed polarity of RecAmediated DNA strand exchange and filament disassembly from DNA relies on ATP hydrolysis to a large extent (Lin Y-H et al 2019). RecA associates more tightly with DNA bound to ATP than with ADP.…”
Section: Strand Invasion Mechanismmentioning
confidence: 99%
“…To study how accepting mismatches in heteroduplex products might influence DSB repair accuracy in vivo , we developed a highly simplified model of homology recognition (see Methods and Materials). The model is informed by experimental results, simulations, modeling, and in vitro experiments (Danilowicz et al, 2015, Sagi et al, 2006, Yang et al, 2015, Bazemore et al, 1997, Cox, 2007, Cox and Lehman, 1981, Lin et al, 2019, Qi et al, 2015, Hsieh et al, 1992, Prentiss et al, 2015, Lee et al, 2015). The model is designed to demonstrate how effectively a highly mismatch tolerant RecA could target allelic pairing.…”
Section: Introductionmentioning
confidence: 99%